Butterflies of the high-altitude Atacama Desert: habitat use and conservation - Despland, Emma (Frontiers in Genetics, 2014)
The butterfly fauna of the high-altitude desert of Northern Chile, though depauperate, shows high endemism, is poorly known and is of considerable conservation concern. This study surveys butterflies along the Andean slope between 2400 and 500 m asl (prepuna, puna and Andean steppe habitats) as well as in high and low altitude wetlands and in the neoriparian vegetation of agricultural sites. We also include historical sightings from museum records. We compare abundances between altitudes, between natural and impacted sites, as well as between two sampling years with different precipitation regimes. The results confirm high altitudinal turnover and show greatest similarity between wetland and slope faunas at similar altitudes. Results also underscore vulnerability to weather fluctuations, particularly in the more arid low-altitude sites, where abundances were much lower in the low precipitation sampling season and several species were not observed at all. Finally, we show that some species have shifted to the neoriparian vegetation of the agricultural landscape, whereas others were only observed in less impacted habitats dominated by native plants. These results suggest that acclimation to novel habitats depends on larval host plant use. The traditional agricultural environment can provide habitat for many, but not all, native butterfly species, but an estimation of the value of these habitats requires better understanding of butterfly life-history strategies and relationships with host plants.